Stability analysis of uncertain fractional-order neutral-type delay systems with actuator saturation - Aghayan, Zahra Sadat; Alfi, Alireza; Tenreiro Machado, J. A. (Frontiers of information technology & electronic engineering, 2021)
This study analyzes the problem of robust stability of fractional-order delay systems of neutral type under actuator saturation. A Lyapunov-Krasovskii (LK) function is constructed and conditions of the asymptotic robust stability of such systems are given, which are formulated by linear matrix inequalities (LMIs), using the Lyapunov direct method. An algorithm is introduced to compute the gain of the state feedback controller for extending the domain of attraction. The theoretical results are validated using some numerical examples.